PENGARUH INDEPENDENSI DAN OBJEKTIVITAS AUDITOR TERHADAP KUALITAS AUDITOR DENGAN EFEK DUNNING-KRUGER SEBAGAI VARIABEL MODERASI - Masjunadi, Masjunadi; Anakotta, Fanny Monica; Limba, Franco Benony (Program Studi Akuntansi PSDKU Universitas Pattimura di Kabupaten Maluku Barat Daya, 2024)
The regional inspectorate is responsible for organising general supervision activities of regional government and other tasks assigned by the regional head. However, several cases were found related to weak supervision, one of which was by the Inspectorate of Ambon City. From these problems, the resulting audit quality is not good. In an auditor, the Dunning-Kruger Effect can also arise. The Dunning-Kruger effect is a person's cognitive bias when he tends to overestimate his competence. The purpose of this study was to empirically examine the effect of audit independence and objectivity on audit quality with the dunning-kruger effect as a moderating variable. This research is a type of quantitative research with the population used in this study were 47 auditors at the Maluku provincial inspectorate office and Ambon city inspectorate with saturated sampling technique and data obtained by distributing questionnaires. The variables of this study consisted of Independence (X1), Auditor Objectivity (X2), as independent variables, Audit Quality (Y) as the dependent variable, and the Dunning-Kruger Effect as the Moderation variable. Hypothesis testing in this study uses Moderated Regression Analysis (MRA) with 3 equations. The results of this study are Independence does not affect Audit quality, Objectivity has a positive and significant effect on audit quality. And the Dunning-Kruger Effect is unable to moderate the relationship between audit independence and objectivity on audit quality. However, the Dunning-Kruger Effect in this relationship is classified as a potential moderating variable